Very early increase in nitric oxide formation and oxidative cell damage associated with the reduction of tissue oxygenation is a trait of blast casualties - Žunić Gordana; Romić Predrag; Vučeljić Marina; Jovanikić Olivera (Vojnosanitetski Pregled)
Background. In our previous experimental studies, we found evidence for the increase of nitric oxide (NO) formation immediately after blast injury. In the present study we investigated whether NO overproduction was a trait for the period immediately after blast injury in humans. Concomitant metabolic disturbances were also studied, and compared to the alterations in other traumatized patients. Methods. Blast casualties (group B, n = 13), surgical patients with the hip replacement or fractures, not exposed to blast effects (group S, n = 7) and healthy volunteers as controls (group C, n = 10), were examined. Both arterial and venous blood samples were taken within 6 hours, and 24 hours after blast injuries or surgical procedures, respectively. Plasma levels of nitrite/nitrate (NOx), superoxyde anion (O2.-), sulfhydrils (SH), malondialdehyde (MDA) as well as acid-base status and other biochemical parameters (glucose, urea, creatinine, total proteins, albumin) were measured. Results. Significant, but transient increase in plasma NOx levels occurred only in group B. It was associated with the significant increase of hemoglobin oxygen (sO2) saturation of the venous blood and the concomitant decrease of its arterial - venous difference. In group S the venous sO2 decreased, its arterial - venous difference increased, while NOx levels were within the control limits. In both groups, other parameters of arterial acid-base status were kept within the control limits throughout the examined period. The decrease of SH levels were similar in the examined groups, while the increase of O2 .- was greater in group B. Conclusion. Early NO overproduction was a trait of blast injuries in humans, contributing to the reduction of tissue the oxygenation and intensifying the oxidative cell damage that had to be considered in the therapy of casualties with blast injuries. These alterations were different from those observed in other surgical patients without blast injuries.